Борель: романы - Петров Петр Поликарпович (Золотые россыпи России, 2012)
Экземпляры: ф30 (20200214) / Инвентарный номер: 59046 / Цена: 45.00 / Сис.шифр: Р2 / Авт.знак: П 30 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6